Female-limited X-chromosome evolution effects on male pre- and post-copulatory success - Manat, Yesbol; Lund-Hansen, Katrine K.; Katsianis, Georgios; Abbott, Jessica K. (Biology letters (2005), 2021)
Intralocus sexual conflict arises when the expression of shared alleles at a single locus generates opposite fitness effects in each sex (i.e. sexually antagonistic alleles), preventing each sex from reaching its sex-specific optimum. Despite its importance to reproductive success, the relative contribution of intralocus sexual conflict to male pre- and post-copulatory success is not well-understood. Here, we used a female-limited X-chromosome (FLX) evolution experiment in Drosophila melanogaster to limit the inheritance of the X-chromosome to the matriline, eliminating possible counter-selection in males and allowing the X-chromosome to accumulate female-benefit alleles. After more than 100 generations of FLX evolution, we studied the effect of the evolved X-chromosome on male attractiveness and sperm competitiveness. We found a non-significant increase in attractiveness and decrease in sperm offence ability in males expressing the evolved X-chromosomes, but a significant increase in their ability to avoid displacement by other males' sperm. This is consistent with a trade-off between these traits, perhaps mediated by differences in body size, causing a small net reduction in overall male fitness in the FLX lines. These results indicate that the X-chromosome in D. melanogaster is subject to selection via intralocus sexual conflict in males.